Metazoan diversity and community assemblages in sediments across a Western Pacific Trench-Arc-Basin system: insights from eDNA metabarcoding - Mo, Jing; Li, Xinlong; Mou, Anning; Gao, Ping; Wang, Xuetao; Zhang, Xuelei; Xu, Qinzeng (Frontiers in Marine Science, 2024)
Trench-arc-basin (TAB) systems are widely distributed in the deep sea, yet our understanding of their biodiversity patterns and community assemblages remains limited. In this study, we collected sediment samples from 22 stations across a Western Pacific TAB system and identified 85 families of marine benthos from 15 phyla by using eDNA metabarcoding with the 18S rRNA gene V4 region. Nematodes were the most dominant metazoan taxa followed by echinoderms, arthropods, and annelids. The highest biodiversity and species specificity were observed at stations located near seamounts. The community assemblages were highly heterogeneous in this TAB system, likely induced by the large geographic barriers and the high habitat heterogeneity. Furthermore, the total organic carbon content and median grain size of the sediment drive the overall community composition, and the water depth exerts a significant influence on species richness and abundance. Our results provide insight into benthos diversity and distribution across a TAB system and data for further comparisons and modeling studies.